Mechanisms of lung damage in tuberculosis: implications for chronic obstructive pulmonary disease - Kayongo, Alex; Nyiro, Brian; Siddharthan, Trishul; Kirenga, Bruce; Checkley, William; Lutaakome Joloba, Moses; Ellner, Jerrold; Salgame, Padmini (Frontiers in Cellular and Infection Microbiology, 2023)
Pulmonary tuberculosis is increasingly recognized as a risk factor for COPD. Severe lung function impairment has been reported in post-TB patients. Despite increasing evidence to support the association between TB and COPD, only a few studies describe the immunological basis of COPD among TB patients following successful treatment completion. In this review, we draw on well-elaborated Mycobacterium tuberculosis-induced immune mechanisms in the lungs to highlight shared mechanisms for COPD pathogenesis in the setting of tuberculosis disease. We further examine how such mechanisms could be exploited to guide COPD therapeutics.